Monumentos entrópicos e a paisagem minerária do ferro - Bruno de Guimaraens Amarante (2019)
During these times of rapid and significant anthropic interventions on Earth, this research focuses its attention on mining landscapes in the Iron Quadrangle of Minas Gerais so as to analyze territory transfigurations due to mining industry actions. As a hybrid dialectic between sensitivity and rationality, either in the poetic field made explicit by sculptures, videos or photographs developed during this study, or by tracing paths through analytic comprehension of the complex and transdisciplinary mineral territory, this work puts forward some points of discussion: the acceleration of iron ore exploration; the certainty of limited resources in the short term relativizing the abundance in the present and shortage in the future; the fast alteration of territory integrating natural and social environment; and the concept of “entropy” associated with the unsustainability of contemporary mineral model. From this field of analysis, this research offers meanings to the ruined landscapes in the cited geographic area, being open sky craters, sludge dams, waste dump and marks of the collapsing of dams the places of memory in the present times. Tortuous patrimony being built. Due to these images, devastated landscapes formed by unusual Entropic Monuments will perpetuate this actual moment of excesses and devastations to the next generations.